Saurida golanii, a new deep water lizardfish (Pisces: Synodontidae) from the Gulf of Aqaba, northern Red Sea - Russell, Barry C. (Zootaxa, 2011)
Saurida golanii sp.nov. is described on the basis of eight specimens collected from bottom-set trammel nets in deep water (200–500 m) off Eilat, in the Gulf of Aqaba, northern Red Sea. The new species is characterised by the following combination of characters: lateral-line scales 53–56; transverse scale rows 4½/5½; long pectoral fins (extending beyond a line from origin of pelvic fins to origin of dorsal fin); caudal peduncle compressed (depth greater than width); and pelvic fins unpigmented.